1993
DOI: 10.1002/jctb.280560407
|View full text |Cite
|
Sign up to set email alerts
|

Influence of serum proteins on the kinetics of attachment of vero cells to cytodex microcarriers

Abstract: Abstract:The attachment characteristics of the Vero cell line on microcarriers has been found to be influenced by the serum proteins. Significant quantities of serum proteins were found to be adsorbed on the carrier surface, which resulted in decreased exchange capacity and a lower attachment rate constant. The kinetics of attachment followed primarily first order with respect to the concentration of free cells. With positively charged microcarriers the attachment process exhibited two distinct phases, an init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…The first one was the modulation of PL concentration. The PL percentage was reduced to 0.5% during the first 24 h of culture to increase cell adhesion (Himes and Hu, ; Mukhopadhyay et al , ), and increased to 5% for the remaining culture to boost the ASC proliferation after adhesion. In addition to this modification, Pluronic® F‐68, which is a non‐ionic surfactant, was added to the culture medium as a shear protectant (Gigout et al , ; Hu et al , ; Murhammer and Goochee, ; Wu, ; Wu et al , ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first one was the modulation of PL concentration. The PL percentage was reduced to 0.5% during the first 24 h of culture to increase cell adhesion (Himes and Hu, ; Mukhopadhyay et al , ), and increased to 5% for the remaining culture to boost the ASC proliferation after adhesion. In addition to this modification, Pluronic® F‐68, which is a non‐ionic surfactant, was added to the culture medium as a shear protectant (Gigout et al , ; Hu et al , ; Murhammer and Goochee, ; Wu, ; Wu et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, because other studies demonstrated that cell adhesion to microcarriers was improved using low serum quantity (Himes and Hu, ; Mukhopadhyay et al , ), we decreased the PL percentage to 0.5% at the beginning of the culture. A non‐ionic surfactant, the Pluronic® F68, was also added to the culture medium as a shear protectant (Gigout et al , ; Hu et al , ; Murhammer and Goochee, ; Wu, ; Wu et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, poor cell adhesion on chitosan was attributed to the low ability of this matrix to adsorb fibronectin from serum‐containing solutions (Amaral et al ., ). In the same vein, the major protein adsorbed from serum on Cytodex‐1 MCs seems to be albumin (Mukhopadhyay et al ., ). In contrast, from previous chromatography studies, fibronectin is known to bind specifically on gelatin (or denatured collagen) (Brew and Ingram, ).…”
Section: Discussionmentioning
confidence: 97%
“…In all studies, [8][9][10][11] the number of viable cells in suspension and the number of cells attached to microcarriers was determined using a method first introduced by Sanford et al 12 and later modified by van Wezel 13 and Levine et al 14 For attached cells on microcarriers, a certain volume of 0.1 M citrate and 0.1% crystal violet was added to a representative sample and the number of released and stained nuclei counted in a haemocytometer. The number of attached cells was corrected using the recorded volume of settled microcarriers in the sample as reported by Napapetian et al 15 and Mukhopadhyay et al 16 Kong et al 17 and Wu et al 10 determined a half-life time for cell attachment that did not differ between the two complementary kinetics of cells attachment and decrease in suspension cells. Both authors concluded that the attachment of cells on microcarriers can be described with first-order kinetics.…”
Section: Introductionmentioning
confidence: 99%